2007
DOI: 10.1007/s11199-007-9189-1
|View full text |Cite
|
Sign up to set email alerts
|

Rape Scripts of Low-income European American and Latina Women

Abstract: Rape scripts can affect attributions about rape and recovery from rape. Due to the potential importance of these scripts, it is critical to investigate them among women of diverse backgrounds. In the current investigation, 393 lowincome European American and Latina women completed a questionnaire regarding their ideas about a typical rape. Violence and negative psychological effects on the victim were rated as highly typical of rape. Latinas rated hook-up and date rapes and rapes among individuals in an establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Furthermore, men who watched an R-rated video clip showing women as sexual objects (rather than a cartoon video clip) before reading about a date-rape scenario were more likely to agree that the woman derived pleasure from the rape and "got what she wanted" (Milburn et al 2000). Stereotypic views of date rape were also held by college women and low-income European-American and Latina women, who rated violent assaults by strangers as being more commonplace than assaults in a dating context or within an established relationship (Littleton et al 2007(Littleton et al , 2009.…”
Section: Cultural Scriptsmentioning
confidence: 99%
“…Furthermore, men who watched an R-rated video clip showing women as sexual objects (rather than a cartoon video clip) before reading about a date-rape scenario were more likely to agree that the woman derived pleasure from the rape and "got what she wanted" (Milburn et al 2000). Stereotypic views of date rape were also held by college women and low-income European-American and Latina women, who rated violent assaults by strangers as being more commonplace than assaults in a dating context or within an established relationship (Littleton et al 2007(Littleton et al , 2009.…”
Section: Cultural Scriptsmentioning
confidence: 99%
“…Although researchers and activists have challenged these scripts recent research shows that these scripts persist (Ahrens, Cabral, & Abeling, 2009;Littleton, Breitkopf, & Berenson, 2007;Miller, Canales, Amacker, Backstrom, & Gidycz, 2011;Payne, Lonsway, & Fitzgerald, 1999;Phillips, 2000). In the present study, several nonlabelers reported not calling their experience rape because the man involved was likeable or was from a good family; because they had been drinking, had been alone with the man, or had willingly kissed him; because the attack had not been violent enough; or because they did not fight back hard enough.…”
Section: Matchmentioning
confidence: 99%
“…Indeed, research supports that individuals' ideas about a typical rape (i.e., their rape scripts) often does not match the reality of most rapes. For example, studies of U.S. women's rape scripts support that these scripts often involve a stranger attack and the use of severe violence by the perpetrator (e.g., beating, choking the woman, using a weapon; Littleton et al 2007a;Littleton et al 2009c;Ryan 1988). In contrast, the vast majority of rape victims are at least acquainted with their assailant and only a very small percentage involve the use of severe violence (e.g., McMullin and White 2006).…”
Section: Rape Scriptsmentioning
confidence: 99%
“…In addition, while a sizable percentage of rapes occur when the victim is intoxicated or impaired due to voluntary ingestion of alcohol (e.g., Littleton et al 2009b;Zinzow et al 2010), this possibility is mentioned much less frequently in individuals' rape scripts, and when it is, the focus is often on the perpetrator drugging the victim by slipping something in her drink (Littleton et al 2009c). Finally, individuals' rape scripts rarely involve a perpetrator or victim who had previously engaged in consensual sexual behavior or a rape that started out as a consensual encounter (e.g., Littleton et al 2007a;Littleton et al 2009c;Ryan 1988).…”
Section: Rape Scriptsmentioning
confidence: 99%